ANALISIS MODEL KERJASAMA PEMANFAATAN BARANG MILIK DAERAH DI ACEH - Fathurrahman Anwar (Departemen Manajemen, Universitas Syiah Kuala, 2018)
Because of the lack of fund, a few infrastrutures and facilities that are build by the government of Indonesia are not utilized optimally. To overcome this problem, the government have issued a few regulations that allow the involvement of private sectors in the utilization of the public goods. Public goods utilization partnership is one of the model that serve the gorvernment purpose. In accordance with this policy, the Government of Aceh have to consider this option to maximize the utilization of the existing asset. Related to the above suggestion, this research will uncover the model of partnership that is feasible and viable to be implemented by the government of Aceh. This reseach will focus on the potential implementation of public goods utilization partnership to optimize the utilization of feedlot facilitiy that is currently organized by UPTD BIB Ie Suum. Data were collected and analyze using investment performance analysis including Internal Rate of Return (IRR), NetPresent Value (NPV), Pay Back Period (PBP), and Profitability Index (PI). The reseach shows that the proposed model is financially feasible for both the government and the private partner. KeywordPublic goods, Public Private Partnership, Internal Rate of Return, Net Present Value, Payback Periode, Profitability Index, Net Income, Free Cash Flow